A QoS-Satisfied Prediction Model for Cloud-Service Composition Based on a Hidden Markov Model. (30th July 2013) - Wu, Qingtao; Zhang, Mingchuan; Zheng, Ruijuan; Lou, Ying; Wei, Wangyang
Abstract : Various significant issues in cloud computing, such as service provision, service matching, and service assessment, have attracted researchers' attention recently. Quality of service (QoS) plays an increasingly important role in the provision of cloud-based services, by aiming for the seamless and dynamic integration of cloud-service components. In this paper, we focus on QoS-satisfied predictions about the composition of cloud-service components and present a QoS-satisfied prediction model based on a hidden Markov model. In providing a cloud-based service for a user, if the user's QoS cannot be satisfied by a single cloud-service component, component composition should be considered, where its QoS-satisfied capability needs to be proactively predicted to be able to guarantee the user's QoS. We discuss the proposed model in detail and prove some aspects of the model. Simulation results show that our model can achieve high prediction accuracies.